Numerical modelling of the RF plasma production in URAGAN-2М stellarator with crankshaft antenna - Moiseenko, V.Е.; Stadnik, Yu.S.; Volkov, E.D.; Schvets, O.M. (Вопросы атомной науки и техники, 2006)
The qualitative technique of the analysis of the efficiency of the RF plasma production is presented in which the
solution of boundary problem for Maxwell’s equations is only necessary. The analysis of the character of the plasma
production process with the crankshaft antenna in Uragan-2M stellarator is carried out. The discussion of the
calculations results is presented. Представлена качественная методика анализа эффективности создания плазмы высокочастотными полями, в
рамках которой необходимо только лишь решение уравнений Максвелла. Проведен анализ характера процесса
создания плазмы в установке Ураган-2М с помощью антенны типа коленвал. Приведено обсуждение
результатов расчетов. Представлено якісну методику аналізу ефективності створення плазми високочастотними полями, в межах
якої необхідне лише розв`язання рівнянь Максвелла. Проведено аналіз характеру процесу створення плазми в
установці Ураган-2М за допомогою антени типу коленвал. Приведено обговорення результатів розрахунків.